Supply chain: Crisp and fuzzy aspects - Fazel Zarandi, Mohammad Hossein; Türkşen, Ismail Burhan; Saghiri, Soroosh (Zielona Góra: Uniwersytet Zielonogórski)
This survey presents crisp and fuzzy models developed for the Supply Chain (SC). To this end, fuzzy concepts are first briefly reviewed. Then the structure of a supply chain system is explained. Recent challenges and ideas on these systems are also surveyed.
Keywords: supply chain; crisp and fuzzy systems; SC system; material flow; information flow; supplier-buyer relationships